P-112 An interview is not a consultation: the dual role of clinician-researcher. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Rainsford, Suzanne; Phillips, Christine
Abstract : Qualitative research into the experience of dying patients and their families frequently includes in-depth interviews or participant observation. Traditionally, clinicians are discouraged from conducting such research among their own patients or in their own practices. Yet barring the clinician from researching their patients, especially where access to non-associated research participants is limited, may represent a lost opportunity to benefit from the experience of clinicians. In this presentation we reflect on our own experience as clinicians and qualitative researchers, drawing on an ethnographic study in which a palliative medicine specialist (first author) studied dying patients and their families in the rural community in which she also lived and practiced. We examine the advantages and disadvantages of 'insider' research and suggest strategies to address the ethical risks and conduct authentic, credible research. Local, prior knowledge and insight, and established rapport and trust, provided depth to the interviews with terminally ill patients and their family caregivers. The risks of power imbalance, recruitment coercion, and filtering of participants' responses required specific management. Clinician-researchers must, at all times, be conscious of their dual role, and conscientiously separate medical management and prior knowledge from the research interviews. Recommendations include the use of an independent third party to obtain informed consent; using iterative consent methods prior to, and after, each interview; using peer support for clarity of role; and maintaining strict boundaries between the researchers' clinical and researcher roles. Clinician researchers must fully declare conflicts of interests with colleagues to reassure them that the researcher is not taking over care of the patient. We found that by using this conscious and conscientious stance, we were able to conduct nuanced, multifaceted research which respected and illuminated the experience of the patient, and their family, often revealing aspects of themselves that they had not shown to us as clinicians.